Multi-Beam Large Fundamental Mode Neodymium Glass Regenerative Amplifier With Uniform Performance - Gao, Song; Xie, Xudong; Tang, Jun; Fan, Chen; Fu, Xuejun; Chen, Zhifei; Yao, Ke (Frontiers in Physics, 2022)
In this paper, the designing method of multi-beam regenerative amplifiers with repetitive rate was proposed and demonstrated. To obtain multi-beam regenerative amplifier with uniform performance, the disparities of output energy, energy stability and mode size were analyzed, and the detailed optimizing method was presented. With the designs, eight-beam regenerative amplifiers were developed. The output performances of eight-beam regenerative amplifiers were uniform. The output energies were in the range of 25.4 mJ 28.8 mJ, and the energy stabilities over two hours were 2.4% 5.1% (PV) and 0.3% 0.9% (RMS).